2020
DOI: 10.1111/1365-2435.13662
|View full text |Cite
|
Sign up to set email alerts
|

Range‐extending tropical herbivores increase diversity, intensity and extent of herbivory functions in temperate marine ecosystems

Abstract: Climate change is modifying species distributions around the world, forcing some species poleward, where they can alter trophic interactions. Many tropical herbivorous fishes have successfully expanded their ranges into temperate ecosystems, and while it is clear they drive increases in herbivory rates in specific localities, little is known about how they might affect the diversity of herbivory functions across large spatial scales, considering their interaction with assemblages of native herbivores in temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
(89 reference statements)
1
24
0
Order By: Relevance
“…Our findings also have key implications concerning ongoing range expansions of herbivorous fishes, which can have transformative impacts on biogenic habitats such as kelp forests and seagrass meadows (Hyndes et al., 2016; Vergés et al., 2014, 2016, 2019; Zarco‐Perello et al., 2017, 2020). First, our results suggest that herbivorous fishes colonizing new habitats are not subject to unique thermal constraints as would be expected if low temperatures imposed a general disadvantage on plant digestion.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings also have key implications concerning ongoing range expansions of herbivorous fishes, which can have transformative impacts on biogenic habitats such as kelp forests and seagrass meadows (Hyndes et al., 2016; Vergés et al., 2014, 2016, 2019; Zarco‐Perello et al., 2017, 2020). First, our results suggest that herbivorous fishes colonizing new habitats are not subject to unique thermal constraints as would be expected if low temperatures imposed a general disadvantage on plant digestion.…”
Section: Discussionmentioning
confidence: 72%
“…It has been proposed that thermal constraints drive global patterns of fish biodiversity based on the observation that the abundance and diversity of herbivorous fishes relative to all fishes decline with increasing latitude and decreasing temperature (Ferreira et al., 2004; Floeter et al., 2004, 2005; Gaines & Lubchenco, 1982; Meekan & Choat, 1997). This relationship between temperature and the distribution of herbivorous fishes is of critical interest because of herbivorous fishes’ potential to have profound impacts on community structure and ecosystem function, as shown by recent poleward expansions in the distribution of marine herbivorous fishes and the ‘tropicalization’ of marine ecosystems (Hyndes et al., 2016; Vergés et al., 2014, 2016, 2019; Zarco‐Perello et al, 2020, 2017). A commonly invoked explanation for the relative rarity of herbivorous fishes at high latitudes is the temperature constraint hypothesis, which proposes that herbivorous fishes have greater difficulty than carnivorous fishes meeting their nutritional requirements with decreasing temperature due to constraints on digestion (Ferreira et al., 2004; Floeter et al., 2004, 2005; Gaines & Lubchenco, 1982; Harmelin‐Vivien, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A surveyor swam at a constant pace parallel to the reef crest for 15 min (~2,000 m 2 ) registering the abundance and the specific habitat where individuals of adult and juvenile herbivorous fish were encountered, completing two transects parallel to each other, ~20 m apart, per day. Fish abundance is reported as density (fish counts 2,000 m −2 ) and as the highest school sizes (MaxS; individuals per school, ind per school) found during surveys (Zarco‐Perello et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The abundance and diversity of herbivores in several temperate regions of the world are increasing due to the poleward range extension of tropical species as a result of the intensification of warm currents that transport tropical propagules to higher latitudes (Vergés et al., 2014). This has increased the intensity and the functional diversity of herbivory (Zarco‐Perello et al., 2020), accelerating the transformation of kelp and other macrophytes to detrital biomass (Zarco‐Perello et al., 2019). While there is no clear evidence at this point that range‐extending tropical herbivores have been the primary cause of shifts to canopy‐free states, there is clear evidence that they have increased kelp consumption, contributing to reduce kelp abundance (Bennett et al., 2015; Vergés et al., 2016; Zarco‐Perello et al., 2017) and maintenance of turf‐dominated states (Bennett et al., 2015) with predictions of further increases of consumption under future warmer conditions (Vergés et al., 2019; Zarco‐Perello et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These studies would be especially key for vulnerable conservation areas, such as national parks and wildlife refuges (McClenachan et al 2020). An interesting ecosystem-level example by Zarco-Perello et al (2020) reported that tropicalization is occurring faster in marine systems than in terrestrial habitats.…”
Section: Accepted Articlementioning
confidence: 99%